Becoming agroecologists: A pedagogical model to support graduate student learning and practice - Nicklay, Jennifer A.; Perrone, Sharon V.; Wauters, Vivian M. (Frontiers in Sustainable Food Systems, 2023)
Introduction Agroecology has multiple beginnings in diverse knowledge systems, growing practices, and social movements which, as a whole, seek systemic transformation to build just food system futures. As graduate students, we have been inspired by agroecological movements and practitioners and endeavored to build our knowledge and capacities as agroecologists. Over the course of seven years, we have worked collectively with an evolving cohort to build relationships, understand critical lineages, and practice participatory processes that we found necessary for our development as agroecologists at the University of Minnesota-Twin Cities. Building on this work, we sought to refine an emergent understanding of the necessary components of an agroecological pedagogy. Methods We thus hosted a series of workshops in summer 2019 to facilitate collective reflection and development of a pedagogy, which we further refined through collective autoethnography. Results The resulting model contains five key components: a cohort at the heart of the model to facilitate collective learning; critical inquiry as the foundation of knowledge production; relational centering as the basis for building and maintaining care-based relationships with self and others; participatory practice as a space for taking action through and within relationships; and situated knowledge to recognize the unique and incomplete knowledge that each individual brings to their work. Discussion We imagine this model as the basis for a dedicated agroecology graduate program, and we close by sharing ongoing implementation efforts, key areas for further development, and our hopes for continued integration with broader movements. Ultimately, we have experienced this process as a transformational agroecological space and hope others are inspired to adapt, imagine, and enact the process, model, and principles in their own places and communities.